OPTIMASI KINERJA TURBIN PELTON RESPON KEMIRINGAN BUCKET DENGAN DIAMETER NOSEL MENGGUNAKAN SOFTWARE STATISTIKA - Rizky Gunawan; Junaidi Junaidi; Fadly Kurniawan (Jurnal Simetri Rekayasa, 2020)
Pelton turbine is a type of impulse turbine that converts all water energy into velocity energy before entering the turbine runner. The power generated in the water turbine (Pelton turbine) varies depending on the flow or flow of incoming water to turn the turbine.This research was conducted in the mechanical engineering laboratory of the Faculty of Mechanical Engineering, Universitas Harapan Medan. The experimental method is the method used in this study. Pelton Turbine performance optimization of bucket slope response and nozzle diameter using statistical software. Based on the results of the Pelton Turbine Testing Graph using the Taguchi method, the response of the bucket slope with the Maximum Rotation nozzle diameter, namely at -8º Bucket slope, produces a turbine rotation of 416.7 Rpm with a nozzle diameter of 19 mm. while with maximum power, the bucket tilt of 8º produces a turbine load of 405 watts with a diameter of 19 mm.